PENGARUH FAKTOR PENDORONG RANTAI PASOK TERHADAP INISIATIF GREEN SUPPLY CHAIN DAN EFEKNYA TERHADAP KINERJA LINGKUNGAN DAN BISNIS - Hasudungan, James; Yunus, Erlinda N. (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
Currently, stakeholders continuously encourage companies to implement green supply chain management (GSCM) to reduce negative impact to environment. In this research, there are 4 drivers of green supply chain(GSC), consist of regulatory measures, customer pressures, competitor pressures, and socio-cultural responsibility. These GSC drivers was then used as variables to determine their impact on GSCM practice in Indonesian manufacturing companies. Despite the influence of GSC drivers on GSCM implementation, this research also seeks for the impact of GSCM implementation to company environmental and business performance. The sampling method utilized was purposive sampling method. This research used online questionnaire to collect the data and SmartPLS 4.0 as a tool to process data. This result reveals that regulatory measures, customer pressures, and socio-cultural responsibility give positif influence for GSCM implementation. However, this research found that competitor pressures have no impact to GSCM implementation in Indonesian manufacturing companies. GSCM implementation have positif impact for company environmental and business performance.